From DEVS to RTA-DEVS - Saadawi, H; Wainer, G (2010 IEEE/ACM 14th International Symposium on Distributed Simulation and Real Time Applications, 2010)
Rational Time-Advance DEVS (RTA-DEVS) is an extension to DEVS that enables formal verification of simulation models using standard model-checking algorithms and tools. In order to enable formal verification of DEVS models, we introduce a procedure to approximate DEVS with RTA-DEVS. We include conditions for valid approximation and a calculation method for approximation errors that may be introduced. The resulting RTA-DEVS models are behaviorally equivalent to the original DEVS.